Your future as a minister - Floyd, William A., 1928- (New York, R. Rosen Press, 1969)
Describes the educational requirements for and the advantages and disadvantages of a career as a minister.
Cover title: A definitive study of your future as a minister.
Bibliography: p. 152-158.
Keywords: Clergy -- Office; Clergy